Study of Neutrophil-Lymphocyte ratio (NLR) in diabetes mellitus - Umarani M. K; Keerti Sahi; Bharathi M. (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Diabetes mellitus is a systemic disease having serious microvascular complications. Neutrophil-lymphocyte ratio (NLR) provides insight about subclinical inflammation and thus acts as a prognostic marker for diabetes mellitus and it's vascular complications.Aim: To study the relationship between neutrophil-lymphocyte ratio with different grades of glucose intolerance. Materials and Methods Cases for the present study include known cases of diabetes mellitus and normal subjects from KR hospital, Mysuru. Fasting blood glucose (FBS) and postprandial blood glucose (PPBS) of study subjects are taken into account to grade glucose intolerance under three categories- Normal glucose tolerance, Impaired glucose tolerance, and diabetes mellitus. Neutrophil-lymphocyte ratios are calculated and compared with blood glucose levels.Results: NLR showed no significant variation in different grades of glucose intolerance. NLR was increased in patients with neuropathy, glaucoma, and blurring of vision when compared with those patients without any complication.Conclusion: NLR is increased in subjects having diabetes mellitus with complications when compared to the subjects with diabetes mellitus under control. Hence NLR can be considered as an early and prognostic marker for microvascular complications in patients with diabetes mellitus.